PENGARUH SELF ACTION DAN SELF EFFICACY TERHADAP KREATIVITAS MAHASISWA DALAM KEGIATAN PRAKTIKUM BIOLOGI UMUM JURUSAN PENDIDIKAN BIOLOGI FAKULTAS TARBIYAH DAN KEGURUAN UIN ALAUDDIN MAKASSAR - Muh Tauhid; Safei Safei; Muhammad Yusuf Hidayat (Jurnal Biotek, 2016)
This research is aimed to find out description self action,  selfefficacy,  and of students’ creativity also to effect of self actionand self efficacy towards the students’ creativity in general biology practical lab.The population of this research was the all students of Biology Education Department, UIN Alauddin Makassar starting from 2012 generation until 2015 generation that consist   11 classes with amount of 400 students. While the sample have taken  by used  of  Simple Random Samplingtechnique,sothatthis research  obtained74 students. The Instrument was used questioner. Data analysis technique was used descriptive statistic and inferential technique.The results of this research through descriptive analysis obtained mean score for self action was 70,20 in the medium category, mean score of self efficacy was 45,28 in the medium category, and mean score of students’ creativity was  51,93 in the medium category. Inferential statistic analysis results with F tes obtained that score Fcount>Ftable (13,778>3,13). Thus, it can be concluded that there is significant effect between self action and self  efficacy towards  students’ creativity in  general  biology practical  lab  at  Biology Education Department of UIN Alauddin Makassar.